Cyclopropene fatty acids in Gnetum gnemon (L.) seeds and leaves - Berry, Shiv K. (John Wiley & Sons, 1980)
The seeds and leaves of Gnetum gnemon (L.), a Gymnosperm, were examined for their fatty acid composition by gas‐liquid chromatography, infrared, ultraviolet and nuclear magnetic resonance spectroscopy. They were found to contain cyclopropene fatty acids (CPFA) determined as silver nitrate derivatives of their esters. ‘Keropok’, a product prepared from seeds, was also examined for its CPFA content. The values (area%) for total CPFA were 51.62, 37.87 and 46.91% of the total fatty acids in the oil of seeds, leaves and keropok, respectively. The effect of normal cooking temperatures on the retention of CPFA in these materials was also investigated.